MAKSIMASI KEUNTUNGAN USAHA PUKAT CINCIN DI NEGERI LATUHALAT PADA MUSIM TIMUR - Willem Talakua; Eygner Gerald Talakua (Universitas Pattimura, 2018)
The purpose of this study is to study the maximization of business profits through the determination of the optimal use of production factors in the trawl ring business in Latuhalat. Observations and direct interviews based on questionnaires were carried out on 3 fishermen who owned trawl ring businesses in 3 hamlets in Latuhalat. Data were analyzed using business profit analysis methods and linear programming analysis. The results showed that: 1). The optimal use of production factors for trawling by the respondents in Latuhalat is 41 - 45 trips in June using 15.2 - 21.1 liters of gasoline, 280.9 - 304.4 liters of gasoline, 10.1 - 21 , 2 liters of oil, using labor as much as 15-17 people for 8 hours / day, and using transportation and FAD services as much as 351.3 - 360 HOK or 8 hours per day; and 2). The maximum profit that can be obtained from trawling rings by respondents in Latuhalat is Rp. 165,545,500 - up to Rp. 184,800,000, - in June. To achieve this maximum profit, respondents need to produce 25,270.3 kg of fish to 27,540.98 kg in June.